Sodium electric hard carbon negative electrode material and preparation method and application thereof

CN122540852BActive Publication Date: 2026-11-03ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611044036.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-11-03
Estimated Expiration
2046-07-14

AI Technical Summary

Technical Problem

Existing technologies struggle to prepare high-performance sodium-ion battery hard carbon anode materials at low cost, as they suffer from problems such as difficulty in precisely controlling pore structure, low initial coulombic efficiency, numerous surface defects, and high process complexity.

Method used

A combined fermentation method using Trichoderma reesei and Yersinia lipolyticis was adopted. By degrading biomass fiber through cellulase system and enriching lipids through the growth and metabolism of Yersinia lipolyticis in the pores, multi-level pore formation, in-situ carbon coating and pore structure regulation were achieved, simplifying the process.

Benefits of technology

A sodium-ion battery hard carbon anode material with high coulombic efficiency, high plateau capacity and excellent rate performance was prepared for the first time, simplifying the process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122540852B_ABST
    Figure CN122540852B_ABST
Patent Text Reader

Abstract

The application provides a kind of sodium electricity hard carbon negative material and its preparation method and application, belong to sodium ion battery negative material technical field.The method includes the following steps: (1) biomass is crushed to obtain powder; (2) the powder is inoculated with trichoderma reesei fermentation culture; (3) inoculate yarrowia lipolytica for secondary fermentation, after inactivation, drying to obtain precursor; (4) the precursor is pre-carbonized and acid washed to obtain pre-carbonized product; (5) high temperature carbonization treatment obtains hard carbon negative material.The application realizes the integration of "pore making-soft carbon coating-secondary pore structure regulation" in the fermentation process through the division of labor and synergistic effect of two kinds of microorganisms, which not only improves the carbon yield, but also prepares hard carbon material with hierarchical pore structure of soft and hard carbon intercalation.The obtained material has high specific capacity when used as sodium ion battery negative electrode, and shows excellent cycle stability and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of sodium-ion battery anode materials, specifically relating to a method for preparing sodium-ion battery hard carbon anode materials using Trichoderma reesei and Yersinia lipolyticis, as well as the products and applications thereof. Background Technology

[0002] Currently, sodium-ion batteries are considered a highly promising alternative technology for large-scale energy storage and specific electric vehicle applications due to the abundance of sodium resources, low cost, environmental friendliness, high safety, and similar working principle to lithium-ion batteries. In sodium-ion batteries, the anode material is a key component for achieving reversible sodium-ion insertion and extraction, or alloying and conversion reactions. Hard carbon materials, due to their large interlayer spacing, rich pore structure, and high sodium storage capacity, are among the most promising anode materials for sodium-ion batteries. However, traditional hard carbon materials (such as petroleum coke and pitch) still suffer from low initial coulombic efficiency, lag in the low-voltage plateau region, and high precursor costs.

[0003] At present, the methods for preparing hard carbon materials using biomass mainly include direct carbonization and activation pore formation, but they generally suffer from problems such as difficulty in precisely controlling the pore structure, numerous surface defects, and low initial coulombic efficiency, and secondary pore formation is usually costly. In response to the above problems, researchers have proposed a variety of solutions, such as using acid or alkali for pore formation, precise spatial confinement processes, and chemical vapor deposition for carbon coating. For example, the literature [1] (Wang Kunfang et al., “Spatial confinement carbonization induces microcrystal and nanopore recombination, carbon framework enhances sodium platform storage”, Advanced Energy Materials, 2025, Vol. 15, No. 24, Document No. 2405294) discloses a method to precisely control the closed pore structure by filling a quantitative amount of coal tar into nanopores, thereby enhancing the sodium storage capacity of the sodium ion platform region, but its raw material input is large, the process consistency requirements are high, and the equipment maintenance cost is expensive, making it difficult to achieve industrialization. Microbial pore formation is a green, mild and controllable bioprocessing method, showing good application potential. For example, in the field of activated carbon preparation, literature [2] (Zhang Weixia, “Microbial targeted degradation pretreatment: a new method for preparing activated carbon with specific hierarchical porous structure, high specific surface area and good toluene adsorption performance”, Environmental Science and Technology, 2019, Vol. 53, No. 13, pp. 7632-7640) disclosed a method for preparing activated carbon with specific hierarchical porous structure and high specific surface area through microbial targeted degradation pretreatment strategy. The authors selected three different fungi, Proteobacterium chrysosporum, Vibrio vulgaris and Aspergillus tabernae, to pretreat the material and obtained porous carbon with mesopores (2~50nm) as the main component, micropores (<2nm) as the main component and medium pore size distribution as the main component. Studies have shown that although activated carbon with different pore structures can be achieved by simply changing the species of bacteria used for degradation, secondary pore structure regulation is still required.

[0004] Therefore, single microorganisms often struggle to simultaneously achieve efficient multi-level pore formation and secondary pore structure regulation. In summary, developing a strategy that integrates efficient pore formation with in-situ carbon coating to achieve a unified process of "pore formation ~ soft carbon coating ~ secondary pore structure regulation" is of significant importance for the development of low-cost, high-performance hard carbon anodes for sodium batteries.

[0005] In recent years, researchers have attempted to improve the pore structure of hard carbon materials by using microorganisms to pretreat biomass. For example, using cellulose-degrading bacteria such as Trichoderma reesei (CN121405070A) to treat biomass can introduce pores into the material by selectively degrading cellulose and hemicellulose. However, single microbial pretreatment has the following limitations: (1) it can only achieve simple "subtractive pore creation" (i.e., removing some components and leaving pores), and cannot actively regulate the pore structure in a secondary manner; (2) some biomass components are consumed during the microbial degradation process, resulting in a decrease in carbon yield; (3) the initial coulombic efficiency of the obtained hard carbon material is still low (usually <85%), which is difficult to meet the needs of commercialization.

[0006] Other studies have attempted to use combined microbial strains for the co-processing of biomass. For example, the co-fermentation of *Trichoderma reesei* and *Yarrowia lipolytica* has been used for the resource utilization of traditional Chinese medicine residues (CN120347049A). *Trichoderma reesei* decomposes cellulose to produce soluble sugars, while *Yarrowia lipolytica* accumulates oils under anaerobic conditions, achieving simultaneous efficient cellulose decomposition and microbial oil production. However, the target products of this type of co-fermentation technology are oils and extracts such as flavonoids. The process conditions are optimized to maximize oil yield, and the fermentation product (oil) is considered the target product to be extracted rather than the functional component to be retained. There are fundamental technical obstacles to directly transferring such technologies to the field of hard carbon anode material preparation: (1) The target products are completely different - the former pursues the extraction and separation of oils and fats, while the latter pursues the in-situ retention and carbonization conversion of oils and fats; (2) The key to optimizing the performance of hard carbon is the appropriate retention of oils and fats rather than the maximum accumulation. Excessive oils and fats will lead to an excessively thick soft carbon coating layer after carbonization, which will hinder the transport of sodium ions; (3) The existing composite fermentation process does not involve the core issue of "how to control the spatial distribution of oils and fats in the biomass matrix to optimize the pore structure".

[0007] Furthermore, the preparation of existing biomass-based hard carbon typically requires secondary pore-forming processes such as acid / alkali etching and template removal after carbonization. These processes not only increase production costs and complexity but also damage the active functional groups on the hard carbon surface, impairing the material's sodium storage performance. Therefore, developing an integrated method that can simultaneously achieve efficient pore-forming, in-situ carbon coating, and secondary pore structure regulation in a single processing step is of significant practical importance for the industrialization of low-cost, high-performance sodium-electric hard carbon anode materials. Summary of the Invention

[0008] In view of the shortcomings of the prior art, the present invention aims to provide a method for preparing sodium-ion battery hard carbon anode material. By combining the effects of two microorganisms, Trichoderma reesei and Yersinia lipolyticis, the method integrates efficient multi-level pore formation and in-situ carbon coating into a "pore formation-soft carbon coating-secondary pore structure regulation" process, thereby preparing a hard carbon anode material with multi-level pore structure, high specific capacity and excellent cycle stability.

[0009] This invention uses biomass raw materials as a carbon source. It involves co-culturing *Trichoderma reesei* through fermentation followed by inoculation with *Yarrowia lipolytica*, followed by inactivation and two-step carbonization to prepare hard carbon materials. The cellulase system secreted by *Trichoderma reesei* efficiently degrades cellulose and hemicellulose in biomass fibers, creating nanoscale pores in the cell walls, achieving pore creation in a single step. Simultaneously, it provides fermentable sugars for *Yarrowia lipolytica*. Utilizing the sugars provided by *Trichoderma reesei* and the lipid components of the raw materials themselves, *Yarrowia lipolytica* grows within the loosened cell cavities, accumulating lipid products (such as triglycerides and fatty acids) during metabolism. These products adhere to the material surface and the interior of the pores, thus enriching the carbon source and ensuring a high carbon yield. In the subsequent carbonization process, the lipids enriched by the metabolism of *Yersinia lipolytica* play two roles: (1) lipids attached to the biomass can be converted into a carbon coating layer, increasing the structural stability of the hard carbon material; (2) lipids accumulated in the pores can be converted into a pore structure regulation layer, which can perform secondary regulation of the pore structure of hard carbon and optimize charge transfer in the electrochemical reaction process. At the same time, the cells of the two microorganisms can serve as biological templates, playing a physical occupancy role in the loose cell cavity and realizing secondary pore formation. The combined action of *Trichoderma reesei* and *Yersinia lipolytica* not only achieves efficient multi-level pore formation, but also performs in-situ carbon coating on hard carbon, and at the same time performs secondary regulation of the pore structure, optimizing its charge conduction and structural stability. Through this method, sodium-electric hard carbon anode materials with high initial coulombic efficiency, high plateau capacity and excellent rate performance can be prepared.

[0010] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a sodium-ion battery hard carbon anode material includes the following steps: (1) The biomass raw materials are crushed to obtain powder; (2) Inoculate the powder obtained in step (1) with Trichoderma reesei ( Trichoderma reesei The Trichoderma reesei fermentation precursor was obtained by fermentation culture. (3) Inoculate the Trichoderma reesei fermentation precursor obtained in step (2) with Yersinia lipolytica ( Yarrowia lipolytica The precursor was obtained by co-fermentation culture, followed by inactivation and drying after fermentation. (4) The integrated processing precursor obtained in step (3) is pre-carbonized under an inert atmosphere, then acid washed and purified to remove ash and impurities, and dried to obtain the purified pre-carbonized product. (5) The purified pre-carbonized product obtained in step (4) is subjected to high-temperature carbonization under an inert atmosphere to obtain hard carbon anode material.

[0011] By employing the above-mentioned technical solution, this invention utilizes the co-fermentation culture of *Trichoderma reesei* and *Yarrowia lipolytica*. On one hand, the cellulase system of *Trichoderma reesei* enables initial pore formation of the biomass raw material; on the other hand, the growth and metabolism of *Yarrowia lipolytica* within its loose cell cavities enriches lipids and, with the aid of a cell template, achieves secondary pore formation, thereby effectively increasing the closed pore volume and improving the initial coulombic efficiency and plateau capacity. Through two-step high-temperature carbonization, the lipids enriched by *Yarrowia lipolytica* are transformed into a dense, highly conductive carbon coating layer, reducing the material's specific surface area, minimizing side reactions, and improving rate performance. This invention combines microbial co-pore formation with in-situ carbon coating to prepare a sodium-based hard carbon anode material with excellent electrochemical performance.

[0012] The following are preferred technical solutions of the present invention: Preferably, in step (1), the biomass raw material is at least one of bamboo, walnut shell, sugarcane, wheat straw, peanut shell, corn cob, pomelo peel, and banana peel; more preferably, the bamboo is at least one of moso bamboo, sclerophylla, or basil; and even more preferably, the bamboo is 2 to 3 years old.

[0013] Preferably, in step (1), before pulverizing, the biomass raw materials can undergo pretreatment steps such as washing, impurity removal, and drying. Preferably, the impurity removal involves: after washing, soaking in clean water for 12-24 hours, changing the water 2-3 times during the process, to dissolve the salt on the surface of the raw materials and create a suitable environment for microbial fermentation. Preferably, in step (1), the drying conditions are: placing the above materials in an oven at a temperature of 75-95°C for a drying time of 6-18 hours.

[0014] Preferably, in step (1), the particle size of the powder obtained after crushing is 0.1~5 mm, more preferably 2~5 mm.

[0015] Preferably, in step (2), the powder and Trichoderma reesei spore suspension are mixed in a preset ratio for fermentation culture; wherein the preset ratio of powder to Trichoderma reesei spore suspension is 1~100g:1mL, more preferably 10g:1mL; and the spore concentration of Trichoderma reesei spore suspension is 1×10⁻⁶. 8 per mL.

[0016] Preferably, in step (2), the temperature for Trichoderma reesei fermentation is 25-30 °C, the humidity is 50%-60%, the pH is 5-6, the fermentation time is 1-7 days, more preferably 2-5 days, the material is turned over 1-3 times every 24 hours, and the fermentation method is solid-state fermentation or liquid-state deep fermentation. More preferably, the culture medium is a modified Mandels solid-state induced fermentation medium, and the carbon source of the culture medium is a mixture of powder and wheat bran in a mass ratio of 10:1.

[0017] Preferably, in steps (2) and (3), the initial inoculation ratio of *Trichoderma reesei* and *Yersinia lipolytica* is 1:5 to 1:15 (based on spore count or colony-forming units), the temperature for co-fermentation is 25 to 30 °C, the ambient humidity is 50% to 60%, the ambient pH is 5 to 6, the culture time is 1 to 10 days, more preferably 5 to 10 days, the material is turned over 1 to 3 times every 24 hours, and the fermentation method is solid-state fermentation or liquid-state deep fermentation. More preferably, in step (3), the whole material after fermentation in step (2) is used as the culture medium, that is, *Yersinia lipolytica* is directly inoculated onto the whole material after fermentation in step (2); more preferably, growth factors are also added, preferably yeast extract, to further ensure the activity of the two strains and ensure the smooth progress of the co-culture of the two strains.

[0018] Preferably, in step (3), the inactivation method is high-temperature inactivation, more preferably, high-temperature inactivation at 105 °C for 2 hours. After inactivation, no washing is performed to retain microbial residues. After drying, a porous precursor containing microbial residues is obtained. More preferably, the drying conditions are as follows: the above material is placed in a water-heated oven at a temperature of 75~95 °C for a drying time of 6~18 hours.

[0019] Preferably, in step (4), the pre-carbonization treatment temperature is 300~800 ℃ and the treatment time is 1~10 h. More preferably, the pre-carbonization conditions are: a heating rate of 2~10 ℃·min. -1 The heat preservation temperature is 300~600 ℃, and the heat preservation time is 2~4 h.

[0020] Preferably, in step (4), the concentration of the acid solution used for pickling is 0.5~2 mol / L, more preferably 1 mol / L, and even more preferably hydrochloric acid solution; the pickling time is 1~6 h, the stirring speed is 150~500 rpm, and the processing temperature is 20~80 ℃. More preferably, the drying conditions are that the above material is placed in a water-heated oven at a temperature of 75~95 ℃ for a drying time of 6~18 h.

[0021] Preferably, in steps (4) and (5), the inert atmosphere is at least one of argon, nitrogen, and helium.

[0022] Preferably, in step (5), the high-temperature carbonization temperature is 1000~1600 ℃, and the carbonization time is 2~10 h. More preferably, the high-temperature carbonization conditions are: a heating rate of 2~10 ℃·min. -1 The heat preservation temperature is 1000~1500 ℃, and the heat preservation time is 2~8 h.

[0023] Preferably, in step (5), the sodium-electric hard carbon anode material obtained has a specific surface area of ​​10~200m². 2 g -1 The average diameter of the closed pores is 0.5–2.5 nm, the carbon yield is 5–30%, and the closed pore volume is 0.01–0.3 m³. 3 g -1 The carbon interlayer spacing is 0.36~0.60 nm, and more preferably the carbon coating layer thickness is 0~2 nm.

[0024] The present invention also protects the sodium-ion battery hard carbon anode material prepared by the above method, and the application of the sodium-ion battery hard carbon anode material in sodium-ion batteries, such as a sodium-ion battery anode containing the material and the sodium-ion battery.

[0025] Based on the above technical solution, compared with the prior art, the present invention has the following beneficial effects: (1) Microbial synergistic division of labor and joint action, functional integration: During the carbonization process, the lipids enriched by the metabolism of Yersinia lipolytica play two roles: (1) Lipids attached to the biomass can be converted into a carbon coating layer, increasing the structural stability of hard carbon materials; (2) Lipids accumulated in the pores can be converted into a pore structure regulation layer, which can perform secondary regulation of the pore structure of hard carbon and optimize charge transfer in the electrochemical reaction process. At the same time, the cells of the two microorganisms can serve as biological templates, playing a physical occupancy role in the loose cell cavity and realizing secondary pore creation. The combined action of Trichoderma reesei and Yersinia lipolytica not only achieves efficient multi-level pore creation, but also performs in-situ carbon coating on hard carbon, and performs secondary regulation of the pore structure, optimizing its charge conduction and structural stability. Through this method, sodium-ion hard carbon anode materials with high initial coulombic efficiency, high plateau capacity and excellent rate performance can be prepared. This method realizes the integration of "pore creation ~ soft carbon coating ~ secondary pore structure regulation" in the same fermentation process, which simplifies the process and reduces costs.

[0026] (2) No external carbon source is required. The oily residues enriched by Yersinia lipolyticis are used to form a carbon coating layer in situ during the carbonization process. It is worth noting that the oily residues enriched by Yersinia lipolyticis are a type of carbon that is easily graphitized. During the carbonization process, soft carbon is formed, which forms a soft-hard interlocking structure with the hard carbon obtained from the carbonization of the biomass raw material itself. This improves the carbon yield and facilitates the conduction and storage of sodium ions. This method simplifies the process and further reduces costs.

[0027] (3) Tight interface bonding: The coating layer formed by in-situ carbonization of Yersinia lipophila residue has a tight interface bonding with the hard carbon matrix, which is beneficial to electron transport and interface stability, and improves the first coulombic efficiency and cycle life. Attached Figure Description

[0028] Figure 1 SEM images of the hard carbon anode material prepared in Example 1; Figure 2 SEM images of the hard carbon anode material prepared in Example 1; Figure 3 SEM images of the hard carbon anode material prepared in Example 1; Figure 4 The image shows the XRD pattern of the hard carbon anode material prepared in Example 1. Figure 5 The diagram shows the cycle capacity of sodium-ion batteries assembled with the hard carbon anode materials prepared in Example 1 and Comparative Examples 1-4 under different rate conditions. Detailed Implementation

[0029] To better clarify and understand the objectives, process solutions, and advantages of this invention, the technical solutions and implementation methods of this invention will be further described clearly, completely, and in detail below through specific embodiments and in conjunction with the accompanying drawings. It should be understood that the embodiments described in this invention are implemented under the premise of the technical solutions of this invention, providing detailed implementation methods and specific operating procedures, but are only some embodiments of this invention, not all embodiments. The specific implementation methods described are limited to illustrating and explaining this invention and do not limit this invention. Based on the embodiments of this invention, all other implementation methods obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0030] Unless otherwise specified, the experimental methods and conditions used in the embodiments of this invention are conventional methods and conditions. The materials, reagents, instruments, and equipment used in the embodiments, unless otherwise specified, are all conventional substances or equipment known to those skilled in the art and can be obtained commercially or prepared by conventional methods. The reaction conditions described in the invention's content can all achieve the stated reactions and obtain the desired products. Due to space limitations, some embodiments are listed below to further illustrate the advantages of the technical solution of this invention.

[0031] The *Trichoderma reesei* used in the following examples and comparative examples were purchased from Ningbo Mingzhou Biotechnology Co., Ltd.; and *Yersinia lipolyticis* was purchased from Wuhan Huana Biotechnology Co., Ltd. However, this is not limited to the specific information described herein; any substance or instrument with equivalent efficacy can achieve the technical solutions and effects described in this invention.

[0032] Example 1 (1) Clean the 2-3 year old moso bamboo to remove surface ash, soak it in water for 12 h to remove surface salt, change the water twice in between, wash it with deionized water, dry it at 80 ℃ for 12 h, crush and sieve it to obtain bamboo powder with a particle size of 2-5 mm.

[0033] (2) Take 100 g of bamboo powder and inoculate it with 10 ml of spore suspension at a concentration of 1×10⁻⁶. 8 A suspension of *Trichoderma reesei* spores per mL was cultured using solid-state fermentation at 28 °C and 55% relative humidity for 48 hours, with the medium being turned over every 24 hours and the pH maintained at 6, to obtain the *Trichoderma reesei* fermentation precursor. The culture medium was a modified Mandels solid-state induced fermentation medium, formulated as follows: using 250 mL of deionized water as a solvent, it contained a carbon source, a nitrogen source, inorganic salts, and a buffer. The amounts of each component were: 100 g bamboo powder, 10 g wheat bran (combined as a composite carbon source), 2 g ammonium sulfate (nitrogen source), 3 g potassium dihydrogen phosphate (buffer), and 0.5 g of the composite inorganic salt MgSO4·7H2O.

[0034] (3) Inoculate the Trichoderma reesei fermentation precursor from step (2) with 10 ml of spore suspension at a concentration of 1×10⁻⁶. 9 Yeast lipolytica (initially inoculated at a ratio of 1:10 between *Trichoderma reesei* and *Yeast lipolytica*, based on spore count) was co-cultured for 120 hours at 28 °C and 55% relative humidity, with the mixture turned over every 24 hours, maintaining an ambient pH of 6. The culture medium consisted of the following: the whole material after fermentation by *Trichoderma reesei* in step (2), and 0.5 g of yeast extract (growth factor). After fermentation, the material was inactivated at 105 °C for 2 hours without washing to retain microbial residues. After drying, a porous bamboo precursor containing microbial residues was obtained. The drying conditions were 80 °C for 12 hours.

[0035] (4) Place the above precursor in a tube furnace and heat it at 5 °C·min under an argon atmosphere. -1The temperature was raised to 500 ℃ and held for 2 hours for pre-carbonization treatment, which partially carbonized the microbial residues and stabilized the bamboo fiber structure. After natural cooling, the pre-carbonized product was obtained. The pre-carbonized product was placed in a 1 mol / L hydrochloric acid solution and stirred and acid-washed at 60 ℃ and 400 rpm for 3 hours. Then it was filtered, repeatedly washed with deionized water until the pH of the filtrate was neutral, and dried at 80 ℃ for 12 hours to obtain the purified pre-carbonized product.

[0036] (5) The purified pre-carbonized product was subjected to an argon atmosphere at 5 °C·min. -1 Heating to 1300℃ and holding for 4 hours for high-temperature carbonization, at a rate of 10℃·min -1 The bamboo fiber is cooled to room temperature to completely carbonize it into a hard carbon matrix. At the same time, the microbial residue is further carbonized to form a dense carbon coating layer. After cooling, a hard carbon anode material is obtained.

[0037] Example 2 (1) Clean the 2-3 year old moso bamboo to remove surface ash, soak it in clean water for 12 h to remove surface salt, change the water twice in between, wash it with deionized water and dry it at 75 ℃ for 6 h, crush and sieve it to obtain bamboo powder with a particle size of 2-5 mm.

[0038] (2) Take 100 g of bamboo powder and inoculate it with 10 ml of spore suspension at a concentration of 1×10⁻⁶. 8 A suspension of *Trichoderma reesei* spores per mL was cultured using solid-state fermentation at 25 °C and 50% relative humidity for 48 hours, with the culture medium being turned over every 24 hours and the pH maintained at 6, to obtain the *Trichoderma reesei* fermentation precursor. The culture medium was the same as in Example 1.

[0039] (3) Inoculate 10 ml of spore suspension with the Trichoderma reesei fermentation precursor at a concentration of 5×10⁻⁶. 8 Yersinia lipolyticis was inoculated at a concentration of 1:5 (Trichoderma reesei to Yersinia lipolyticis initial inoculum ratio of 1:5) at 25 °C and 50% relative humidity for 120 hours, with the substrate turned over every 24 hours, and the pH maintained at 6. After fermentation, the microorganisms were inactivated at 105 °C for 2 hours without washing to retain microbial residues. The resulting porous bamboo precursor containing microbial residues was dried at 75 °C for 6 hours. The culture medium was the same as in Example 1.

[0040] (4) Place the above precursor in a tube furnace and heat it at 2 °C·min under an argon atmosphere. -1The temperature was raised to 300 ℃ and held for 2 hours for pre-carbonization treatment, which partially carbonized the microbial residues and stabilized the bamboo fiber structure. After natural cooling, the pre-carbonized product was obtained. The pre-carbonized product was placed in a 0.5 mol / L hydrochloric acid solution and stirred and acid-washed at 20 ℃ and 150 rpm for 1 hour. Then it was filtered, repeatedly washed with deionized water until the pH of the filtrate was neutral, and dried at 75 ℃ for 6 hours to obtain the purified pre-carbonized product.

[0041] (5) The purified pre-carbonized product was subjected to an argon atmosphere at 2 °C·min. -1 Heat to 1100℃ and hold for 2 hours for high-temperature carbonization, at a rate of 10℃·min. -1 The bamboo fiber is cooled to room temperature to completely carbonize it into a hard carbon matrix. At the same time, the microbial residue is further carbonized to form a dense carbon coating layer. After cooling, a hard carbon anode material is obtained.

[0042] Example 3 (1) Clean the 2-3 year old moso bamboo to remove surface ash, soak it in clean water for 12 h to remove surface salt, change the water twice in between, wash it with deionized water, dry it at 75 ℃ for 18 h, crush and sieve it to obtain bamboo powder with a particle size of 2-5 mm.

[0043] (2) Take 100 g of bamboo powder and inoculate it with 10 ml of spore suspension at a concentration of 1×10⁻⁶. 8 A suspension of *Trichoderma reesei* spores per mL was cultured using solid-state fermentation at 30°C and 60% relative humidity for 48 hours, with the culture medium being turned over every 24 hours and the pH maintained at 6, to obtain the *Trichoderma reesei* fermentation precursor. The culture medium was the same as in Example 1.

[0044] (3) Inoculate 10 ml of spore suspension with the Trichoderma reesei fermentation precursor at a concentration of 1.5 × 10⁻⁶ ml. 9 Yersinia lipolyticis was inoculated at a concentration of 1 / mL (the initial inoculation ratio of Trichoderma reesei to Yersinia lipolyticis was 1:15). The mixture was co-cultured at 30 °C and 60% relative humidity for 120 hours, with turning every 24 hours, and the pH was maintained at 6. After fermentation, the microorganisms were inactivated at 105 °C for 2 hours without washing to retain microbial residues. The resulting porous bamboo precursor containing microbial residues was dried at 75 °C for 18 hours. The culture medium was the same as in Example 1.

[0045] (4) Place the above precursor in a tube furnace and heat it at 10 °C·min under an argon atmosphere. -1The temperature was raised to 600 ℃ and held for 2 hours for pre-carbonization treatment, which partially carbonized the microbial residues and stabilized the bamboo fiber structure. After natural cooling, the pre-carbonized product was obtained. The pre-carbonized product was placed in a 2 mol / L hydrochloric acid solution and stirred and acid-washed at 80 ℃ and 500 rpm for 6 hours. Then it was filtered, repeatedly washed with deionized water until the pH of the filtrate was neutral, and dried at 75 ℃ for 18 hours to obtain the purified pre-carbonized product.

[0046] (5) The purified pre-carbonized product was subjected to an argon atmosphere at 10 °C·min. -1 Heating to 1500℃ and holding for 8 hours for high-temperature carbonization, at a rate of 10℃·min -1 The bamboo fiber is cooled to room temperature to completely carbonize it into a hard carbon matrix. At the same time, the microbial residue is further carbonized to form a dense carbon coating layer. After cooling, a hard carbon anode material is obtained.

[0047] Example 4 (1) Clean the 2-3 year old moso bamboo to remove surface ash, soak it in clean water for 24 h to remove surface salt, change the water 3 times in between, wash it with deionized water and dry it at 95 ℃ for 6 h, crush and sieve it to obtain bamboo powder with a particle size of 2-5 mm.

[0048] (2) Take 100 g of bamboo powder and inoculate it with 10 ml of spore suspension at a concentration of 1×10⁻⁶. 8 A suspension of *Trichoderma reesei* spores per mL was cultured using solid-state fermentation at 28 °C and 55% relative humidity for 120 hours, with the culture medium being turned three times every 24 hours and the pH maintained at 5, to obtain the *Trichoderma reesei* fermentation precursor. The culture medium was the same as in Example 1.

[0049] (3) Inoculate 10 ml of spore suspension with the Trichoderma reesei fermentation precursor at a concentration of 1×10⁻⁶. 9 Yersinia lipolyticis was inoculated at a concentration of 1:10 (Trichoderma reesei to Yersinia lipolyticis) at 28 °C and 55% relative humidity for 240 hours, with the substrate turned over three times every 24 hours, and the pH maintained at 5. After fermentation, the microorganisms were inactivated at 105 °C for 2 hours without washing to retain microbial residues. The resulting porous bamboo precursor containing microbial residues was dried at 95 °C for 6 hours. The culture medium was the same as in Example 1.

[0050] (4) Place the above precursor in a tube furnace and heat it at 5 °C·min under an argon atmosphere. -1The temperature was raised to 500 ℃ and held for 4 hours for pre-carbonization treatment, which partially carbonized the microbial residues and stabilized the bamboo fiber structure. After natural cooling, the pre-carbonized product was obtained. The pre-carbonized product was placed in a 1 mol / L hydrochloric acid solution and stirred and acid-washed at 60 ℃ and 400 rpm for 3 hours. Then it was filtered, repeatedly washed with deionized water until the pH of the filtrate was neutral, and dried at 95 ℃ for 6 hours to obtain the purified pre-carbonized product.

[0051] (5) The purified pre-carbonized product was subjected to an argon atmosphere at 5 °C·min. -1 Heating to 1300℃ and holding for 4 hours for high-temperature carbonization, at a rate of 10℃·min -1 The bamboo fiber is cooled to room temperature to completely carbonize it into a hard carbon matrix. At the same time, the microbial residue is further carbonized to form a dense carbon coating layer. After cooling, a hard carbon anode material is obtained.

[0052] Example 5 (1) Clean the 2-3 year old moso bamboo to remove surface ash, soak it in clean water for 24 h to remove surface salt, change the water 3 times in between, wash it with deionized water, dry it at 95 ℃ for 18 h, crush and sieve it to obtain bamboo powder with a particle size of 2-5 mm.

[0053] (2) Take 100 g of bamboo powder and inoculate it with 10 ml of spore suspension at a concentration of 1×10⁻⁶. 8 A suspension of *Trichoderma reesei* spores per mL was cultured using solid-state fermentation at 25 °C and 50% relative humidity for 120 hours, with the culture medium being turned three times every 24 hours and the pH maintained at 5, to obtain the *Trichoderma reesei* fermentation precursor. The culture medium was the same as in Example 1.

[0054] (3) Inoculate 10 ml of spore suspension with the Trichoderma reesei fermentation precursor at a concentration of 5×10⁻⁶. 8 Yersinia lipolyticis was inoculated at a concentration of 1:5 (Trichoderma reesei to Yersinia lipolyticis initial inoculum ratio of 1:5) at 25 °C and 50% relative humidity for 240 hours, with the substrate turned over 3 times every 24 hours, and the pH maintained at 5. After fermentation, the microorganisms were inactivated at 105 °C for 2 hours without washing to retain microbial residues. The resulting porous bamboo precursor containing microbial residues was dried at 95 °C for 18 hours. The culture medium was the same as in Example 1.

[0055] (4) Place the above precursor in a tube furnace and heat it at 2 °C·min under an argon atmosphere. -1The temperature was raised to 300 ℃ and held for 4 hours for pre-carbonization treatment, which partially carbonized the microbial residues and stabilized the bamboo fiber structure. After natural cooling, the pre-carbonized product was obtained. The pre-carbonized product was placed in a 0.5 mol / L hydrochloric acid solution and stirred and acid-washed at 20 ℃ and 150 rpm for 1 hour. Then it was filtered, repeatedly washed with deionized water until the pH of the filtrate was neutral, and dried at 95 ℃ for 18 hours to obtain the purified pre-carbonized product.

[0056] (5) The purified pre-carbonized product was subjected to an argon atmosphere at 2 °C·min. -1 Heat to 1100℃ and hold for 2 hours for high-temperature carbonization, at a rate of 10℃·min. -1 The bamboo fiber is cooled to room temperature to completely carbonize it into a hard carbon matrix. At the same time, the microbial residue is further carbonized to form a dense carbon coating layer. After cooling, a hard carbon anode material is obtained.

[0057] Example 6 (1) Clean the 2-3 year old moso bamboo to remove surface ash, soak it in clean water for 24 h to remove surface salt, change the water 3 times in between, wash it with deionized water and dry it at 80 ℃ for 12 h, crush and sieve it to obtain bamboo powder with a particle size of 2-5 mm.

[0058] (2) Take 100 g of bamboo powder and inoculate it with 10 ml of spore suspension at a concentration of 1×10⁻⁶. 8 A suspension of *Trichoderma reesei* spores per mL was cultured using solid-state fermentation at 30 °C and 60% relative humidity for 120 hours, with the culture medium being turned three times every 24 hours and the pH maintained at 5, to obtain the *Trichoderma reesei* fermentation precursor. The culture medium was the same as in Example 1.

[0059] (3) Inoculate 10 ml of spore suspension with the Trichoderma reesei fermentation precursor at a concentration of 1.5 × 10⁻⁶ ml. 9 Yersinia lipolyticis was inoculated at a concentration of 1 / mL (the initial inoculation ratio of Trichoderma reesei to Yersinia lipolyticis was 1:15). The mixture was co-cultured at 30 °C and 60% relative humidity for 240 hours, with the substrate turned three times every 24 hours, and the pH maintained at 5. After fermentation, the microorganisms were inactivated at 105 °C for 2 hours without washing to retain microbial residues. The resulting porous bamboo precursor containing microbial residues was dried at 80 °C for 12 hours. The culture medium was the same as in Example 1.

[0060] (4) Place the above precursor in a tube furnace and heat it at 10 °C·min under an argon atmosphere. -1The temperature was raised to 600 ℃ and held for 4 hours for pre-carbonization treatment, which partially carbonized the microbial residues and stabilized the bamboo fiber structure. After natural cooling, the pre-carbonized product was obtained. The pre-carbonized product was placed in a 2 mol / L hydrochloric acid solution and stirred and acid-washed at 80 ℃ and 500 rpm for 6 hours. Then it was filtered, repeatedly washed with deionized water until the pH of the filtrate was neutral, and dried at 80 ℃ for 12 hours to obtain the purified pre-carbonized product.

[0061] (5) The purified pre-carbonized product was subjected to an argon atmosphere at 10 °C·min. -1 Heating to 1500℃ and holding for 8 hours for high-temperature carbonization, at a rate of 10℃·min -1 The bamboo fiber is cooled to room temperature to completely carbonize it into a hard carbon matrix. At the same time, the microbial residue is further carbonized to form a dense carbon coating layer. After cooling, a hard carbon anode material is obtained.

[0062] Example 7 It is basically the same as Example 1, except that: bamboo is replaced with walnut shells, and the bamboo powder in the culture medium is replaced with an equal mass of walnut shell powder.

[0063] Example 8 It is basically the same as Example 1, except that: bamboo is replaced with sugarcane, and the bamboo powder in the culture medium is replaced with an equal mass of sugarcane powder.

[0064] Example 9 It is basically the same as Example 1, except that bamboo is replaced with wheat straw, and the bamboo powder in the culture medium is replaced with an equal mass of wheat straw powder.

[0065] Example 10 It is basically the same as Example 1, except that: bamboo is replaced with peanut shells, and the bamboo powder in the culture medium is replaced with an equal mass of peanut shell powder.

[0066] Example 11 It is basically the same as Example 1, except that: bamboo is replaced with corn cob, and the bamboo powder in the culture medium is replaced with an equal mass of corn cob powder.

[0067] Example 12 The method is basically the same as in Example 1, except that bamboo is replaced with grapefruit peel and the bamboo powder in the culture medium is replaced with an equal mass of grapefruit peel powder.

[0068] Example 13 It is basically the same as Example 1, except that the bamboo is replaced with banana peel and the bamboo powder in the culture medium is replaced with an equal mass of banana peel powder.

[0069] Comparative Example 1: Direct carbonization of biomass feedstock (1) Clean the 2-3 year old moso bamboo to remove surface ash, soak it in clean water for 12 h to remove surface salt, change the water twice in between, wash it with deionized water, dry it at 80 ℃ for 12 h, crush and sieve it to obtain bamboo powder with a particle size of 2-5 mm.

[0070] (2) Place the above bamboo powder in a tube furnace and heat it at 5 °C·min under an argon atmosphere. -1 The bamboo fiber structure was stabilized by heating to 500 ℃ and holding for 2 hours for pre-carbonization. After natural cooling, the pre-carbonized product was obtained. The pre-carbonized product was placed in a 1 mol / L hydrochloric acid solution and stirred and acid-washed at 60 ℃ and 400 rpm for 3 hours. Then it was filtered, repeatedly washed with deionized water until the pH of the filtrate was neutral, and dried at 80 ℃ for 12 hours to obtain the purified pre-carbonized product.

[0071] (3) The purified pre-carbonized product was subjected to an argon atmosphere at 5 °C·min. -1 Heating to 1300℃ and holding for 4 hours for high-temperature carbonization, at a rate of 10℃·min -1 The bamboo fiber is cooled to room temperature to completely carbonize it into a hard carbon matrix. After cooling, a hard carbon anode material is obtained.

[0072] Comparative Example 2: Trichoderma reesei fermentation only (1) Clean the 2-3 year old moso bamboo to remove surface ash, soak it in clean water for 12 h to remove surface salt, change the water twice in between, wash it with deionized water, dry it at 80 ℃ for 12 h, crush and sieve it to obtain bamboo powder with a particle size of 2-5 mm.

[0073] (2) Take 100 g of bamboo powder and inoculate it with 10 ml of spore suspension at a concentration of 1×10⁻⁶. 8 Trichoderma reesei spore suspension was cultured in a solid-state fermentation process at 28 °C and 55% relative humidity for 48 hours, with the culture medium being turned over once every 24 hours and the pH of the environment being maintained at 6, to obtain the Trichoderma reesei fermentation precursor. The culture medium was the same as step (2) in Example 1.

[0074] (3) After fermentation, the microorganisms were inactivated at 105 °C for 2 hours without washing to retain the microbial residues. After drying, a porous bamboo precursor with microbial residues was obtained.

[0075] The subsequent steps are the same as steps (4) and (5) in Example 1, so that the bamboo fiber is completely carbonized into a hard carbon matrix, and after cooling, a hard carbon anode material is obtained.

[0076] Comparative Example 3: Fermentation with only Yersinia lipophila was performed. (1) Clean the 2-3 year old moso bamboo to remove surface ash, soak it in clean water for 12 h to remove surface salt, change the water twice in between, wash it with deionized water, dry it at 80 ℃ for 12 h, crush and sieve it to obtain bamboo powder with a particle size of 2-5 mm.

[0077] (2) Take 100 g of bamboo powder and inoculate it with 10 ml of spore suspension at a concentration of 1×10⁻⁶. 9 Yersinia lipolyticis was cultured at 28 °C and 55% relative humidity for 120 hours, with the medium being turned over every 24 hours, and the pH of the environment was maintained at 6. The formula of the modified Mandels solid-state induced fermentation medium is as follows: using 250 mL of deionized water as solvent, it contains carbon source, nitrogen source, inorganic salt, and buffer, with the following amounts: 100 g of bamboo powder, 10 g of wheat bran (combined as a complex carbon source), 2 g of ammonium sulfate (nitrogen source), 3 g of potassium dihydrogen phosphate (buffer), and 0.5 g of complex inorganic salt MgSO4·7H2O.

[0078] (3) After fermentation, the microorganisms were inactivated at 105 °C for 2 hours without washing to retain the microbial residues. After drying, a porous bamboo precursor with microbial residues was obtained. The drying conditions were 80 °C and 12 h.

[0079] The subsequent steps are the same as steps (4) and (5) in Example 1, so that the bamboo fiber is completely carbonized into a hard carbon matrix, and the microbial residue is further carbonized to form a dense carbon coating layer. After cooling, a hard carbon anode material is obtained.

[0080] Comparative Example 4: Yersinia lipolyticis was first inoculated, followed by Trichoderma reesei fermentation. (1) Clean the 2-3 year old moso bamboo to remove surface ash, soak it in clean water for 12 h to remove surface salt, change the water twice in between, wash it with deionized water, dry it at 80 ℃ for 12 h, crush and sieve it to obtain bamboo powder with a particle size of 2-5 mm.

[0081] (2) Take 100 g of bamboo powder and inoculate it with 10 ml of spore suspension at a concentration of 1×10⁻⁶. 9A suspension of *Yarrowia lipolyticis* spores per mL was cultured using solid-state fermentation at 28 °C and 55% relative humidity for 48 hours, with the mixture turned over every 24 hours and the pH maintained at 6, to obtain the *Yarrowia lipolyticis* fermentation precursor. The modified Mandels solid-state induced fermentation medium was formulated as follows: using 250 mL of deionized water as the solvent, it contained a carbon source, a nitrogen source, inorganic salts, and a buffer. The amounts of each component were: 100 g bamboo powder, 10 g wheat bran (combined as a composite carbon source), 2 g ammonium sulfate (nitrogen source), 3 g potassium dihydrogen phosphate (buffer), and 0.5 g of the composite inorganic salt MgSO4·7H2O.

[0082] (3) Inoculate 10 ml of spore suspension with the Yersinia lipolytica fermentation precursor at a concentration of 1×10⁻⁶. 8 Trichoderma reesei (initial inoculation ratio of Yersinia lipolyticis to Trichoderma reesei was 1:10) was co-cultured at 28 ℃ and 55% relative humidity for 120 hours, with the material turned over once every 24 hours, and the pH of the environment was maintained at 6. After fermentation, the material was inactivated at 105 ℃ for 2 hours without washing to retain microbial residues. After drying, porous bamboo precursors with microbial residues were obtained. The drying conditions were 80 ℃ and 12 h. The culture medium included the following: the whole material after fermentation in step (2), and 0.5 g of yeast extract (growth factor).

[0083] The subsequent steps are the same as steps (4) and (5) in Example 1, so that the bamboo fiber is completely carbonized into a hard carbon matrix, and the microbial residue is further carbonized to form a dense carbon coating layer. After cooling, a hard carbon anode material is obtained.

[0084] Comparative Example 5: Removal of Microbial Residue The process is basically the same as in Example 1, except that the porous bamboo precursor with microbial residues obtained after drying is subjected to an additional washing operation.

[0085] Comparative Example 6: Other dual-bacterial combination It is basically the same as Example 1, except that Trichoderma reesei and Yeast lipolytica are replaced with Trichoderma reesei and Saccharomyces cerevisiae.

[0086] Comparative Example 7: Other dual-bacterial combination The results are basically the same as in Example 1, except that Trichoderma reesei and Yersinia lipolytica are replaced with Aspergillus niger and Yersinia lipolytica.

[0087] Comparative Example 8 (Patent CN120347049A) directly applied process parameters (maximizing grease). The method is basically the same as Example 1, except that the fermentation conditions of patent CN120347049A (aerobic 48h / 35℃ + anaerobic 72h / 28℃) are used. Bamboo powder was treated at ℃ and then carbonized, with other conditions the same as in the example.

[0088] Results: Excessive oil enrichment resulted in an excessively thick soft carbon coating after carbonization, leading to overfilling of pores. The specific surface area and pore volume of the material decreased significantly, and the initial coulombic efficiency and rate performance were inferior to those of the embodiments of this invention. This demonstrates that the "oil maximization" process parameters of this patent are not applicable to the preparation of hard carbon anode materials, and the selection of process parameters in this invention (such as controlling the degree of oil enrichment within a specific range through specific conditions) is not obvious.

[0089] Test Example: Battery Assembly and Performance Testing Preparation of hard carbon anode material: The hard carbon anode material, conductive carbon black (SP), and polyvinylidene fluoride (PVDF) obtained in the above examples and comparative examples were accurately weighed according to a mass ratio of 8:1:1. These were then placed in N-methylpyrrolidone (NMP) to ensure a solid content of 25%. Next, the mixture was transferred to a homogenizer and homogenized at 1780 rpm. After homogenization, 1 g of the resulting slurry was uniformly coated onto an aluminum foil current collector using a 150 μm scraper, ensuring an active material loading of ~2 mg / cm³. ~2 Subsequently, the coated aluminum foil was first dried in a 70°C forced-air drying oven for 2 hours, and then transferred to a 120°C vacuum drying oven for another 12 hours. After the drying process, the resulting electrode sheet was compacted on a roller press to a thickness of 1 mm. Finally, the compacted electrode sheet was cut into 12 mm diameter pieces to serve as electrode plates.

[0090] Sodium-ion battery assembly: In a glove box filled with argon gas and with humidity and oxygen concentration below 0.01 ppm, the positive electrode shell, the one-piece molded electrode sheets of the above embodiments and comparative examples, the electrolyte (1 mol / L NaPF6 in DME = 100 vol%), the glass fiber separator (Whatman GF / D), the sodium sheet, the gasket, the spring sheet, and the negative electrode shell were assembled in sequence. Finally, a 50 kg cm³ load was applied. -1 Encapsulation is performed under pressure.

[0091] Place the assembled sodium-ion battery on the Xinwei battery tester and test it at a rate of 0.02 A g within the voltage range of 0.01~2.5 V. -1 Activate for three cycles, then use 1 A g -1 Long-cycle testing was conducted. The rate testing used a 0.02 A g... -1 0.05 Ag-1 0.1 A g -1 0.2 A g -1 0.5 A g -1 1 A g -1 0.02 Ag -1 Current density.

[0092] The hard carbon anode material prepared according to the above method is shown in Table 1.

[0093] Table 1

[0094] Combining the data in the table and the appendix Figures 1-4 It can be seen that by first inoculating *Trichoderma reesei* for fermentation and then inoculating *Yersinia lipolytica* for co-culture, the hard carbon anode material obtained through inactivation and two-step carbonization can achieve integrated "pore-forming ~ soft carbon coating ~ secondary pore structure regulation" during fermentation. This effectively regulates the pore structure without reducing the carbon yield, producing a hierarchical pore structure with intercalation of soft and hard carbon. This effectively increases the closed-pore volume, reduces the specific surface area of ​​the material, reduces side reactions, and the smaller specific surface area can improve the first-efficiency, reduce irreversible sodium loss, and extend the cycle life. In contrast, the closed-pore volume of the hard carbon materials obtained in the comparative examples with no inoculation and partial inoculation is significantly reduced, while the specific surface area increases. The low closed-pore volume in comparative examples 1-8 indicates an extreme lack of the cluster-filled sodium storage space characteristic of hard carbon. Sodium ions cannot achieve large-capacity intercalation and storage within the closed cavity, directly leading to a significant loss of the characteristic low-voltage plateau capacity of hard carbon. At the same time, the internal ion buffer and stress regulation space are insufficient, the sodium ion transport kinetics are lagging, and the stability of the electrode structure drops sharply. The low specific surface area of ​​Comparative Example 1 indicates a limited number of active sites and pores, leading to a significant reduction in the adsorption and intercalation capacity of sodium ions. Insufficient pores also hinder electrolyte penetration, resulting in long sodium ion transport paths and severe polarization at high rates. The medium to high specific surface areas of Comparative Examples 2-7 tend to significantly increase the contact area with the electrolyte, triggering uncontrollable SEI film formation, consuming active sodium and electrolyte, and making them prone to pore closure or structural collapse during cycling, leading to rapid capacity decay.

[0095] Meanwhile, the average diameter of the closed pores in the examples and comparative examples ranged from 0.6 to 2.1 nm. Thanks to the synergistic pore-forming and sealing effect of the two bacteria, the material in Example 1 possessed abundant effective closed-pore structures, with a closed-pore volume as high as 0.2 μm. 3 g -1 This provides ample clustered sodium storage space for sodium ions. However, comparative examples 1-3, lacking a dual-strain co-fermentation process, could not construct an effective closed-pore structure; the closed-pore volume of the hard carbon materials was only 0.03-0.06 m³. 3 g-1 Effective closed pores are extremely scarce, with the pore structure dominated by a few open pores and a dense overall structure. Combined with electrochemical performance data, it can be seen that the severe lack of effective closed-pore sodium storage sites leads to low reversible capacity, poor sodium ion filling and transport kinetics, and ultimately significantly limited rate performance. In Comparative Example 2, using only *Trichoderma reesei* to consume cellulose for pore formation significantly reduced the carbon production rate of the hard carbon material. Severe carbon loss during carbonization resulted in a discontinuous residual carbon skeleton and insufficient structural support, making it impossible to construct a stable micropore and closed-pore network. The weak carbon skeleton was prone to structural pulverization and collapse during charge and discharge, leading to a sharp drop in electrode structural stability. Regarding the interlayer spacing of the hard carbon material, the interlayer spacing in the examples was all between 0.37 and 0.50 nm. A suitable interlayer spacing can reduce Na... + This study aimed to improve diffusion resistance, enhance sodium storage capacity, and improve rate and cycle performance, thereby achieving a high-capacity, long-life sodium-ion battery system. In Comparative Example 5, the precursor after dual-microbial co-fermentation was thoroughly washed to remove microbial residues and metabolites, and then carbonized to prepare hard carbon material. The results showed that this treatment completely removed the soft carbon coating layer formed in situ on the material surface, decreased the surface conductivity, increased interfacial charge transport resistance, deteriorated rate performance, intensified interfacial side reactions, and significantly reduced electrode stability.

[0096] Comparative Example 6 used a combination of *Trichoderma reesei* and *Saccharomyces cerevisiae*, and Comparative Example 7 used a combination of *Aspergillus niger* and *Yersinia lipolyticis* for co-fermentation. The results showed that *Saccharomyces cerevisiae* could not grow efficiently in an acidic degradation environment, its metabolic activity was suppressed, it could not effectively control pore sealing, and it could not form a continuous soft carbon coating layer; the pore structure and electrochemical performance were not significantly improved. Excessive degradation of cellulose by *Aspergillus niger* destroyed the biomass skeleton structure, reduced residual carbon yield, and the carbon skeleton after carbonization was loose and discontinuous, unable to construct a stable closed-pore network. The material was prone to structural pulverization and collapse during charge and discharge, and the electrode stability dropped sharply. Comparative Example 8 used the fermentation conditions (aerobic 48h / 35℃ + anaerobic 72h / 28℃) of patent CN120347049A to treat bamboo powder before carbonization, with other conditions the same as in the examples. The results showed that the oil was excessively enriched, the soft carbon coating layer was too thick after carbonization, and the pores were over-filled; the specific surface area and pore volume of the material decreased significantly, and the initial coulombic efficiency and rate performance were inferior to those of the examples of this invention. The existing "grease maximization" process parameters are not applicable to the preparation of hard carbon anode materials, and the selection of process parameters in this invention (such as controlling the degree of grease enrichment within a specific range) is non-obvious.

[0097] The electrochemical properties were prepared and measured according to the above method, and the results are shown in Table 2.

[0098] Table 2 Comparison of electrochemical performance of different hard carbon anode materials

[0099] The materials described in Examples 1-13 of this invention were tested under the test conditions of the test examples, and all met the following requirements: at 0.02A g... -1 The initial discharge specific capacity at current density is not less than 440 mA hg -1 The initial coulomb efficiency is no less than 80%, in 1A g -1 The initial discharge specific capacity at current density is not less than 220 mA hg -1 After 1000 cycles, the discharge specific capacity is not less than 190 mAh g. -1 The cycle capacity retention rate is no less than 85%. In contrast, the battery tested in Comparative Example 1, at 0.02 A g... -1 The batteries tested exhibited low initial discharge specific capacity and coulombic efficiency below 50% at the given current density. Furthermore, the batteries in Comparative Examples 2-4, due to their large specific surface area, experienced a significant increase in the contact area between the active material and the electrolyte, leading to uncontrollable SEI film formation and the consumption of active sodium and electrolyte, resulting in extremely low coulombic efficiency in the first cycle. In summary, Comparative Examples 1-4 all exhibited low capacity retention, poor cycle performance, and poor rate performance.

[0100] The hard carbon anode material obtained in Example 1 was used in a 0.02 A g test. -1 0.05 Ag -1 0.1 A g -1 0.2 A g -1 0.5 A g -1 1 A g -1 0.02 Ag -1 The specific capacitance at the given current density is 469.89 mA hg. -1 365.46mA hg -1 348.21 mA hg -1 331.46mA hg -1 302.18 mA hg -1 263.85 mA hg -1 367.53mA hg -1 The performance of Examples 2-13 shows the same trend as that of Example 1. However, in Comparative Examples 1-4, such as... Figure 5 As shown, the battery capacity is significantly lower than that of the embodiments of the present invention under different current densities, and the coulombic efficiency is low.

[0101] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any way. Other variations and modifications may be made without departing from the technical solutions described in the claims.

Claims

1. A method for preparing a sodium-electric hard carbon anode material, characterized in that, Includes the following steps: (1) The biomass raw materials are crushed to obtain powder; (2) Inoculate the powder with Trichoderma reesei and ferment it to obtain Trichoderma reesei fermentation precursor; the fermentation temperature in step (2) is 25 ~ 30 ℃, the culture time is 1 ~ 7 days, the humidity is 50% ~ 60%, and the pH is 5 ~ 6; turn the material 1 ~ 3 times every 24 hours, and the fermentation method is solid-state fermentation; (3) Inoculate the Trichoderma reesei fermentation precursor with Yersinia lipolytica and ferment it. After fermentation, inactivate and dry it to obtain the integrated treatment precursor. The fermentation temperature in step (3) is 25-30 ℃, the culture time is 1-10 days, the humidity is 50%-60%, and the pH is 5-6. Turn the material 1-3 times every 24 hours. The fermentation method is solid-state fermentation. (4) The integrated processing precursor is pre-carbonized under an inert atmosphere and then acid-washed to obtain the purified pre-carbonized product. (5) The purified pre-carbonized product is subjected to high-temperature carbonization treatment under an inert atmosphere to obtain hard carbon anode material.

2. The method according to claim 1, characterized in that, The biomass raw material mentioned in step (1) is at least one of bamboo, walnut shells, sugarcane, wheat straw, peanut shells, corn cobs, pomelo peels, and banana peels; And / or, the particle size of the powder is 0.1~5mm.

3. The method according to claim 1, characterized in that, The inoculation ratio of Trichoderma reesei to Yersinia lipolytica is 1:5~15; And / or, in step (2), the powder and Trichoderma reesei spore suspension are mixed in a preset ratio for fermentation culture; wherein the preset ratio of powder to Trichoderma reesei spore suspension is 1~100g:1mL; and the spore concentration of the Trichoderma reesei spore suspension is 1×10⁻⁶. 8 per mL.

4. The method according to claim 1, characterized in that, In step (3), no washing is performed after inactivation to retain microbial residues; And / or, the inactivation method in step (3) is high-temperature inactivation.

5. The method according to claim 1, characterized in that, The temperature of the pre-carbonization treatment in step (4) is 300~800 ℃, and the treatment time is 1~10 h; And / or, the concentration of the acid solution used for pickling in step (4) is 0.5 ~ 2 mol / L, the pickling time is 1 ~ 6 h, and the treatment temperature is 20 ~ 80 ℃; And / or, the high-temperature carbonization treatment in step (5) is carried out at a temperature of 1000 ~ 1600 ℃ and for a carbonization time of 2 ~ 10 h.

6. The method according to claim 5, characterized in that, The heating rate of the pre-carbonization treatment in step (4) is 2~10 °C·min. -1 The heat preservation temperature is 300~600 ℃, and the heat preservation time is 2~4 h; And / or, the heating rate of the high-temperature carbonization treatment in step (5) is 2~10 °C·min. -1 The heat preservation temperature is 1000~1500 ℃, and the heat preservation time is 2~8 h.

7. The method according to claim 1, characterized in that, The obtained sodium-ion hard carbon anode material has a specific surface area of ​​10~200 m². 2 g -1 The average diameter of the closed pores is 0.5~2.5 nm, and the carbon interlayer spacing is 0.36~0.60 nm.

8. A sodium-electric hard carbon anode material prepared by the preparation method according to any one of claims 1 to 7.

9. The application of a sodium-ion battery hard carbon anode material prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Fermentation method of traditional Chinese medicine residues

    CN120347049A

  • Method for preparing sodium-ion battery hard carbon negative electrode material through microbial degradation of biomass

    CN121405070A